2003
DOI: 10.1177/030089160308900311
|View full text |Cite
|
Sign up to set email alerts
|

The Nipple-Sparing Mastectomy: Early Results of a Feasibility Study of a New Application of Perioperative Radiotherapy (Eliot) in the Treatment of Breast Cancer When Mastectomy is Indicated

Abstract: These preliminary results are encouraging but they require further studies to evaluate the long-term results, the local recurrence rate and the psychological impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…This suggests that despite the lack of pectoral muscle protection in the group of delayed radiotherapy, the patients did not show an increasing rate of capsular contracture. Many authors underline the possibility of NAC preservation without ELIOT [13,[20][21][22][23][24][26][27][28][29]. The lack of difference in the local recurrence rate between our study and others studies published should question the need of radiotherapy.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This suggests that despite the lack of pectoral muscle protection in the group of delayed radiotherapy, the patients did not show an increasing rate of capsular contracture. Many authors underline the possibility of NAC preservation without ELIOT [13,[20][21][22][23][24][26][27][28][29]. The lack of difference in the local recurrence rate between our study and others studies published should question the need of radiotherapy.…”
Section: Discussionmentioning
confidence: 46%
“…Since 2002, a growing number of patients received this new treatment modality, termed nipple sparing mastectomy (NSM). Our preliminary results of NSM were published in 2003 [20]. Here, we report the results of the first 1,001 patients.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…From the oncological point of view recent studies [12][13][14][22][23][24] and a recent review of the literature [25] showed that the risks and complications of NSM, with or without ELIOT, were acceptable, when compared to the traditional surgical treatment of breast cancer and NSM can be considered as a viable option in the appropriate setting.…”
Section: Discussionmentioning
confidence: 99%
“…Results were published by Petit et al [12][13][14]. The effect of removal of the NAC during mastectomy and of nipple reconstruction procedures has not been often studied; Wellisch et al [15] demonstrated the positive psychological impact of NAC reconstruction after mastectomy and breast reconstruction when comparing patients with or without NAC reconstruction.…”
Section: Introductionmentioning
confidence: 99%